PENTINGNYA PENGUASAAN BAHASA ASING SEBAGAI SALAH SATU PENDUKUNG FAKTOR UTAMA INDUSTRI PARIWISATA - Dewi, Ni Putu Sasmika (Institut Agama Hindu Negeri Gde Puda Mataram, 2023)
Mastery of a foreign language is an absolute must for tourism actors and communities in tourism areas, but in reality there are still many tourism actors and communities in tourism areas that still don’t care how importance to mastering foreign languages. The aims of this article is to find out the role of foreign languages and also the reasons why foreign languages are important for tourism actors and communities in tourism areas to master. This article was written using the literature method where what is seen are phenomena related to foreign languages. The analysis result show that foreign languages really need to be mastered by tourism actors and communities in tourism areas because foreign languages play an important role. tourism promotion, reservation services, tourism services and guiding services. Apart from that, it is important for people in tourism areas to master a foreign language to exchange culture, build the community's own economy, improve the positive image of the area where tourism is located, expand employment opportunities and also build broad connections.